Gaza in Peril: Navigating the Humanitarian Crisis - Mamat, Mafeitzeral (International Journal of Human and Health Sciences (IJHHS), 2025)
Gaza is in the midst of destruction; the worst ever humanitarian crisis the world have ever seen in the modern era with no end in sight. Since October 7, 2023, more than 42,000 people have been killed and at least 98,000 injured in Gaza. Recent escalations across the Middle East have resulted in dire humanitarian conditions in Gaza worsened as the attention is diverted elsewhere. There is no positive solution to the forced mass displacement, widespread food insecurity, insufficient shelter and the obvious significant civilian casualties. Severe food insecurity has permeated the Strip, with rampant hunger turning into famine – a catastrophe already present. Three-quarters of Gazans rely on food assistance for survival, according to the World Food Programme (WFP). Efforts to address the humanitarian crisis have faced increasing impossible challenges. Aid deliveries to Gaza have reached their lowest levels in months. Israeli authorities have implemented a new customs regulation on certain types of humanitarian aid and are also reducing shipments arranged by businesses. Gaza is unrecognisable, with homes, schools, and hospitals having been reduced to rubble. There is not enough food or clean water, and the healthcare system has all but collapsed. Almost every single person in Gaza has fled their homes. There is nowhere safe left to go. International Journal of Human and Health Sciences Supplementary Issue 01: 2025 Page: S9